Maize consumption estimation and dietary diversity assessment methods in Malawi - Mazunda, John; Droppelmann, Klaus (International Food Policy Research Institute, 2012)
Food security in Malawi is generally equated with adequate maize production, the country’s main staple crop, which accounts for more than 60 percent of total food production. However, reliable estimates of maize consumption are also useful measures for assessing food security. Further, information on the level of dietary diversity in the country can be used by policymakers and program managers to evaluate progress towards nutrition goals. This policy brief is based on a triangulation exercise evaluating alternative data sources for estimating maize availability and consumption as proxy measures of food security in Malawi. Data sources used for the comparison estimates include the Integrated Household Survey, the Food and Agriculture Organization’s Food Balance Sheets, and documentation from the Malawi office of the World Food Programme (WFP) and the Malawi Vulnerability Assessment Committee. The brief also examines how best to use information from the country’s second Integrated Household Survey to assess the level of dietary diversity in Malawi as a measure of nutrition security. Comparative statistics are applied to assess the reliability and accuracy of available production, consumption, and dietary diversity data, with particular emphasis on maize.